2017
DOI: 10.1098/rsfs.2016.0149
|View full text |Cite
|
Sign up to set email alerts
|

Sampling and tracking a changing environment: persistence and reward in the foraging decisions of bumblebees

Abstract: The question of when to collect new information and how to apply that information is central to much of behaviour. Theory suggests that the value of collecting information, or sampling, depends on environmental persistence and on the relative costs of making wrong decisions. However, empirical tests of how these variables interact are lacking. We tested whether bumblebee foraging decisions are indeed influenced by these two factors. We gave bees repeated choices between a resource providing a steady, mediocre … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 75 publications
0
15
0
1
Order By: Relevance
“…For example, when floral displays are highly heterogeneous, carry-over effects (a preference for signals similar to known rewarding ones) may keep visitors foraging on flowers that resemble rewarding ones [45], as mentioned in §3a. Additionally, foragers' attempts to adjust acceptance thresholds in response to frequent changes in PDF overlap could inflict high learning costs, or require extra assessment to make adaptive choices [64]. These learning and assessment costs could prevent flower foragers from adjusting acceptance thresholds.…”
Section: (I) Floral Resource Heterogeneitymentioning
confidence: 99%
“…For example, when floral displays are highly heterogeneous, carry-over effects (a preference for signals similar to known rewarding ones) may keep visitors foraging on flowers that resemble rewarding ones [45], as mentioned in §3a. Additionally, foragers' attempts to adjust acceptance thresholds in response to frequent changes in PDF overlap could inflict high learning costs, or require extra assessment to make adaptive choices [64]. These learning and assessment costs could prevent flower foragers from adjusting acceptance thresholds.…”
Section: (I) Floral Resource Heterogeneitymentioning
confidence: 99%
“…Hildesheim et al 2019;Kalisz & Vogler 2003;Moreira-Hernandez & Muchhala;Opedal et al 2016) and studies have examined how reliability of floral rewards affects pollinator behavior (e.g. Austin et al 2019;Dunlap et al 2017); however, how stochasticity in the presence of pollinators affects floral evolution and the delineation of pollination systems remains a largely understudied topic. Future studies testing the pollination syndrome concept should utilize plant-pollinator data with broad spatiotemporal coverage when defining primary pollinators and consider how pollinator reliability across time and space may influence the interpretation of pollination syndromes (or the lack thereof) in their focal species.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies on nectarivores have been carried out on bees. Results have, however, been unclear, possibly due to the previously described binomial interpretation of risk (Shafir 2000;Weber et al 2004): bees have been observed to be risk-indifferent (Banschbach and Waddington 1994;Perez and Waddington 1996;Fülöp and Menzel 2000), risk-averse (Waddington et al 1981;Shapiro 2000), to follow the budget rule (Cartar and Dill 1990;Cartar 1991), or a mixture of those depending on risk variability (Shafir et al 1999;Shafir 2000;Mayack and Naug 2011;Dunlap et al 2017). Bees and other eusocial insects represent a special case for risk sensitivity.…”
Section: Ants As a Model For Risk Sensitivitymentioning
confidence: 99%